Peningkatan efesiensi administrasi desa melalui pelatihan mail merge di Kantor Desa Langko - Islam, Ikhlas Nurul; Rodi, Muhamad (Penamas: Journal of Community Service, 2025)
Efficient village administration is crucial for delivering fast and accurate public services. One major challenge is the manual document preparation process, which is time-consuming and prone to errors. This community service activity aims to enhance administrative efficiency by training village officials at the Langko Village Office in using Mail Merge in Microsoft Word. The training employed a hands-on approach with four participants from the village administration. Evaluation was conducted by comparing pre-test and post-test results to measure improvement in participant skills. The findings indicate that the training successfully accelerated document preparation by 70%, reduced typing errors from 60% to 5%, and increased participants' skill scores from an average of 35 to 92.5. Furthermore, the training contributed to standardizing document formats, thereby enhancing professionalism in village governance. These results highlight the potential of technology adoption in improving administrative effectiveness and data accuracy. Further community service activity is recommended to expand the training scope by involving more participants and integrating more advanced data management technologies to support the digitalization of village administration.